3′-epi-12β-hydroxyfroside-mediated autophagy degradation of RIPK1/RIPK3 necrosomes leads to anergy of immunogenic cell death in triple-negative breast cancer cells. (January 2023) - Huang, Feng-Ying; Dai, Shu-Zhen; Xu, Wen-Tian; Xiong, Wei; Sun, Yan; Huang, Yong-Hao; Wang, Jin-Yan; Lin, Ying-Ying; Chen, Hengyu; Tan, Guang-Hong; Zheng, Wu-Ping
Abstract: Increasing studies have suggested that some cardiac glycosides, such as conventional digoxin (DIG) and digitoxin, can induce immunogenic cell death (ICD) in various tumors. We previously found that 3′-epi-12β-hydroxyfroside (HyFS), a novel cardenolide compound isolated by our group, could induce cytoprotective autophagy through inactivation of the Akt/mTOR pathway. However, whether HyFS can induce ICD remains unknown. In this study, we extend our work to further investigate whether HyFS could induce both autophagy and ICD, and we investigated the relationship between autophagy and ICD in three TNBC cell lines. Unexpectedly, compared to DIG, we found that HyFS could induce complete autophagy flux but not ICD in three human triple-negative breast cancer (TNBC) cell lines and one murine TNBC model. Inhibition of HyFS-induced autophagy resulted in the production of ICD in TNBC MDA-MB-231, MDA-MB-436, and HCC38 cells. A further mechanism study showed that formation of RIPK1/RIPK3 necrosomes was necessary for ICD induction in DIG-treated TNBC cells, while HyFS treatment led to receptor-interacting serine-threonine kinase (RIPK)1/3 necrosome degradation via an autophagy process. Additionally, inhibition of HyFS-induced autophagy by the autophagy inhibitor chloroquine resulted in the reoccurrence of ICD and reversion of the tumor microenvironment, leading to more significant antitumor effects in immunocompetent mice than in immunodeficient mice. These findings indicate that HyFS-mediated autophagic degradation of RIPK1/RIPK3 necrosomes leads to inactivation of ICD in TNBC cells. Moreover, combined treatment with HyFS and an autophagy inhibitor may enhance the antitumor activities, suggesting an alternative therapeutic for TNBC treatment. Graphical Abstract: Treatment with digoxin induces phosphorylation and subsequent assembly of RIPK1 and RIPK3 to form necrosomes, leading to the phosphorylation of MLKL. The phosphorylation-mediated activation of MLKL and subsequent MLKL-mediated membrane pore formation result in immunogenic cell death, as evidenced by the surface expression of CRT and secretion of sHMGB1 and ATP. However, treatment with HyFS induces autophagy degradation of RIPK1 and RIPK3 necrosomes, preventing the formation of MLKL-mediated membrane pores and thus resulting in anergy of immunogenic cell death. ga1